Measuring, modelling and testing ozone exposure, flux and effects on vegetation in southern European conditions--what does not work? A review from Italy. (Environmental pollution (Barking, Essex : 1987), 2007)
Ozone (O3) exposure at Italian background sites exceeds UN/ECE concentration-based critical levels (CLe(c)), if expressed in terms of AOT40. Yet the occurrence of adverse effects of O3 on forests and crops is controversial. Possible reasons include (i) ability of response indicators to provide an unbiased estimate of O3 effects, (ii) setting of current CLe(c) in terms of cut-off value and accumulation level, (iii) response functions adopted to infer a critical level, (iv) environmental limitation to O3 uptake and (v) inherent characteristics of Mediterranean vegetation. In particular, the two latter points suggest that critical levels based on accumulated stomatal flux (CLe(f)) can be a better predictor of O3 risk than CLe(c). While this concept is largely acknowledged, a number of factors may limit its applicability for routine monitoring. This paper reviews levels, uptake and vegetation response to O3 in Italy over recent years to discuss value, uncertainty and feasibility of different approaches to risk assessment.

Ozone uptake by an evergreen Mediterranean Forest () in Italy. Part I: Micrometeorological flux measurements and flux partitioning (Atmospheric Environment, 2005)
Ozone, water and energy ﬂuxes have been measured over a Mediterranean evergreen forest in Central Italy from August to October 2003 with the eddy-correlation technique in order to evaluate the amount of ozone taken up by plants in dry summer and in mild autumn conditions. The stomatal ozone ﬂuxes have been calculated using the analogy with water vapor ﬂuxes inside the stomata, which are easily measurable. The total ozone dose was obtained by integrating the stomatal ﬂuxes over time. Stomatal ﬂux resulted a minor part (31.5%) of the total ozone ﬂux over the forest ecosystem. The main part of ozone deposition follows non-stomatal pathways. Chemical sink seems to play a relevant role in the morning non-stomatal deposition. Stomatal uptake is enhanced by water availability but, on the average, it does not exceed the 34.4% of the total ozone ﬂux. A comparison between the cumulated stomatal ozone ﬂuxes and the currently used AOT40 exposure index highlighted important distortions introduced by this index. AOT40, which do not take into account plant physiology, lead to substantial overestimation of ozone risk, particularly when water supply is limited, as occurs frequently in Southern European and Mediterranean areas.

An overview of the Castelporziano experiments (Atmospheric Environment, 1997)
This paper reviews the major outcomes of the measuring campaigns performed at the Castelporziano nature preserve near Rome, Italy, by 14 European laboratories as part of the BEMA (Biogenic Emissions in the Mediterranean Area)-project. Six campaigns of 1–4 weeks duration were carried out in different seasons of the years 1993–1994 at semi-continuously running test plots in the nature reserve, representing common Mediterranean vegetation types. The aim was to characterise, at the different test plots, the atmospheric chemical and meteorological situations, the plant biomass and physiology, the type, amount and controls of emissions from different plants by means of branch enclosures, and the BVOC emission fluxes from different ecosystems, by scaling up enclosure data from individual sources, and by measuring fluxes directly by use of micrometeorological methods. An important focus during the initial phase of the five year BEMA-project was the harmonisation and improvement of the analytical, physiological and micrometeorological methods used, and the development and testing of new methods for measuring BVOC fluxes.